Related Risk Factors of Early Childhood Caries in Zhejiang Province, China During the COVID-19 Pandemic - Huang, Chaoqiang; Zhu, Kangqi; Feng, Yibing; Lian, Luya; Zhu, Haihua; Hu, Jian (Frontiers in Public Health, 2022)
Objectives This work aims to examining the latest early childhood caries situation in children aged 3 and 5 and its related risk factors in Zhejiang Province during the COVID-19 pandemic. Method There are 3,537 children and their main caregivers participate in this study. We used chi square test or U-test to analyze whether there were differences in the prevalence of dental caries under different variables. The risk factors on ECC were determined by multivariate logistic analysis. Results The ECC rate of children in this study was 57.51%. The mean decayed missing filled teeth (dmft) scores were 3.01. The result of multivariate logistic analysis showed higher ECC prevalence was found in children as age increasing, with lower district economic level, with high frequency of confectionary consumption, having oral medical treatment behavior and bad evaluation of children's oral health by parents. Conclusion In general, the prevalence rate of ECC in this study was lower than five years ago, but still higher than those developed countries. And it was associated with age, district economic level, frequency of confectionary consumption, oral medical treatment behavior and evaluation of children's oral health by parents.